Potensi Kebun Raya Indrokilo Sebagai Daya Tarik Ekowisata Di Kabupaten Boyolali - Titik Akiriningsih; Yolan Wahyu Decxyvano (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aimed to determine to potential of Indrokilo Boyollai Botanical Garden as an ecotourism attraction in terms terms of the A4 tourist attraction components (Attraction, Accessibility, Amenity, Ancillary) and the optimization of Indrokilo Botanical Garden as an ecotourism attraction. This research used qualitative descriptive approach and SWOT analysis. Data collection in this study was carried out by observing and interviewing the Management of Indrokilo Boyolali Botanical Garden, equipped with documentation and literature study. The result of this research of Indrokilo Botanical Garden has the potential to be used an ecotourism attraction since it has several attractive objects and supporting facilities with the concept of conservation or environmental preservation and educational value. The optimization carried out by management of the Indrokilo Botacinal Garden is to present tourism activities in an attractive form and optimize infrastructure development that has not been realized to support tourism activities in Indrokilo Botanical Garden.